2000
DOI: 10.1046/j.1523-1755.2000.00107.x
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal blood pressure and 24-hour pulse pressure are potent indicators of mortality in hemodialysis patients

Abstract: This study demonstrates that nocturnal BP and 24-hour PP are independent predictors of CV mortality in treated hypertensive hemodialysis patients. Randomized trials are needed to investigate whether nocturnal BP and 24-hour PP are superior to office BP as targets for antihypertensive therapy in this high-risk group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
168
3
6

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(185 citation statements)
references
References 28 publications
8
168
3
6
Order By: Relevance
“…The effect of these factors in patients who undergo maintenance HD is likely to intensify over time. Increased arterial stiffness and elevated PP are strong independent predictors of all-cause mortality and mainly cardiovascular mortality among patients with ESRD (27)(28)(29)(30). Taken together, this may explain the correlation between PP and hazard for death in patients with Ͼ10 yr of HD.…”
Section: Discussionmentioning
confidence: 85%
“…The effect of these factors in patients who undergo maintenance HD is likely to intensify over time. Increased arterial stiffness and elevated PP are strong independent predictors of all-cause mortality and mainly cardiovascular mortality among patients with ESRD (27)(28)(29)(30). Taken together, this may explain the correlation between PP and hazard for death in patients with Ͼ10 yr of HD.…”
Section: Discussionmentioning
confidence: 85%
“…It has been reported that ambulatory blood pressure monitoring (ABPM) data in dialysis patients are a better predictor for development of LVH and cardiovascular mortality than casual blood pressure (BP) measurements. 4,5 Casual BP measurements are far from being ideal to reflect BP levels precisely in dialysis patients and adjusting antihypertensive treatment according to casual BP measurements may cause an inadequate BP control. ABPM allows a better assessment in the course of BP levels during the day.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, several studies have reported the relationship between pulse pressure and mortality or cardiovascular events in HD patients (13)(14)(15)(16)(17). In this study, we studied in a prospective cohort whether WAB was a more useful prognostic marker in HD patients than one-point BP measurement and investigated which components of WAB were the most potent marker in evaluating the effect of hypertension on cardiovascular events (CVE) or all-cause mortality in HD patients.…”
mentioning
confidence: 99%